PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KREATIVITAS GURU TERHADAP PRODUKTIVITAS BELAJAR SISWA - Ucu Sumantri (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2020)
The problems in this CAR are as follows: 1) How is the influence of the principal's leadership on student learning productivity? 2) How is the influence of teacher creativity on student learning productivity? As for the objects in this study are the principal's leadership (X1), teacher creativity (X2) and student learning productivity (Y). The research method that I use is descriptive method, descriptive method, namely the method used to look for the elements, characteristics, and properties of a phenomenon. This method begins with collecting data, analyzing data, and interpreting it. In its implementation, it is carried out through: survey techniques, case studies, comparative studies, behavior analysis and documentary analysis. This study tries to describe the reality and facts of the problems studied in depth by looking for factual data from the variables studied, so that the relationship between variables can be analyzed by quantitative analysis through statistical tests using the SPSS 17.0 For Windows program. The research results obtained provide conclusions 1) There is a significant influence of the principal's leadership of 19.89% on student learning productivity. This means that the better the leadership of the principal, the better the student's learning productivity. 2) There is a significant effect of teacher creativity at 17.89% on student learning productivity. This means that the better the teacher's creativity, the better the student's learning productivity. 3) There is a significant effect of principal leadership and teacher creativity by 62.5% on student learning productivity. This means that the better the principal leadership and teacher creativity, the better student learning productivity.